Pemetaan dan Penentuan Produk Unggulan Daerah Kota Pekalongan - Wenti Ayu Sunarjo; Ari Muhardono; Amalia Ilmiani (JURNAL LITBANG KOTA PEKALONGAN, 2025)
Development focuses on sectors that are capable of driving regional progress that can be detailed into superior regional products. This study uses a mix method approach, with analysis techniques in data collection using intramethod mixing and intermethod mixing through questionnaire, interview, and documentation techniques. Data were obtained by means of secondary surveys and questionnaires to 108 people as respondents, obtained as many as 21 candidate superior products selected by the community and selected 10 products that are community priorities and agreed upon by experts including; traditional batik, megono, fish processing, canting tulis and cap crafts, woven crafts, tauco, oriental lemonade drinks, processed tempeh, tea products, and convection. Based on the results of the calculation of the projection for the next 5-20 years using the exponential method, it was found that all products had an increase, but the analysis results were dominated by several superior products that showed rapid development. The order of the results of the projection of superior regional products from the most developed to the least developed products is; (1) traditional batik, (2) tea products, (3) convection, (4) megono, (5) processed tempeh, (6) tauco, (7) oriental lemonade drinks, (8) weaving crafts, (9) fish processing, (10) canting tulis and stamp crafts.